MUTUAL MODERASI KEBERAGAMAN SEBAGAI PRAKTIK BAIK MENUJU SEKOLAH RAMAH ANAK DI SMP SWASTA AL-WASLIYAH KECAMATAN MEDAN SUNGGAL KOTA MEDAN - Baiduri, Ratih; Wahyudi, Arief; Damanik, M.Ridha; Jamaludin, Jamaludin; Anastasya Sihaloho, Oksari (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The goal of the Community Partnership Program (PKM) is to generally respond to the circular on the child-friendly school program from the Medan City Government's Department of Education and Culture through mutual moderation as a good practice towards the child-friendly school program. The profile of the area where the service location is situated is Lalang Village, Medan Sunggal District, Medan City, covering an area of approximately 125 hectares. This village serves as the western gateway to Medan City and is traversed by the Trans-Sumatra Highway. Administratively, Lalang Village consists of 13 neighborhoods. Al-Wasliyah Middle School becomes the partner location for this community program activity. The potential problems found at the junior high school/equivalent education level are intolerance, bullying, and child violence. The solution offered through mutual moderation of diversity towards child-friendly schools makes Medan City a safe and comfortable place for every student by prioritizing tolerance, harmony, and comfort, which are the foundations of mutual moderation in good practices. Encouraging parental involvement in the children's education process, as well as giving special attention to the emotional and social well-being of the students. The method used involves systematic and coherent stages starting from data collection, socialization, education (FGD, research, and study visits), training, and mentoring. (monitoring dan evaluasi). Mutual moderation (or joint moderation) in the context of Child-Friendly Schools can be an effective approach to addressing problems, achieving common goals, and maintaining a positive environment. Through these steps, the process of mutual moderation can become an effective tool for achieving and maintaining a Child-Friendly School environment. It involves active collaboration and positive contributions from all stakeholders